Factors affecting some properties on surface of thermowood material applied with water-based varnishes modifed with nanoparticles - Karamanoğlu, Mehmet; Kesik, Haci İsmail (FapUNIFESP (SciELO), 2021)
ABSTRACT Background: The aim of this study is to determine the surface roughness and adhesion strength of water-based varnishes modified with nanoparticles of zinc oxide (ZnO) and hollow ceramic spherical (HCS) against accelerated UV aging effect in some ThermoWood materials. For this purpose, American ash (Fraxinus americana) and scotch pine (Pinus sylvestris Lipsky) wood were heat treated at a temperature of 190 °C for 1.5 hours and 212 °C for 2 hours. The heat-treated samples were applied with two-component water-based varnishes, with D70 - D99 commercial codes, modified with 1%, 3% and 5% ZnO and HCS nanoparticles individually then these samples were subjected to accelerated aging for 240 hours according to ASTM G154. The surface roughness of varnish layers was determined by TS 6956 EN ISO 4287/A1 and surface adhesion strength by ASTM D4541 principles. Results: The results showed that the nanoparticles generally decreased the surface roughness and adhesion strength in water based varnishes. But surface roughness increased in additives of 5% HCS in D99 and 1% ZnO in D70. Also adhesion strength increased in additives of 5% ZnO and 1% and 5% HCS in D70. Conclusion: The layer properties of water-based varnishes can be improved with ZnO and HCS nanoparticles against aging effects.
Keywords: ceramic sphere; surface roughness; ZnO; adhesion strength.; ZnO, ceramic sphere, surface roughness, adhesion strength.